Enhancing Digital Legal Literacy: Guidance in Formulating Privacy Policies and Terms & Conditions for Micro and Small Enterprises (MSEs) in the Platform Economy Era - Flora, Henny Saida; Ginanjar, Yudha; Ali Syaifudin, Mohamad; Rusmana, Dodi; Pratiwi Puwa, Suryani Intan (Inovasi Pratama Internasional. Ltd, 2026)
The rapid digitalization of Indonesia's economy has created unprecedented opportunities for micro and small enterprises (MSEs) to participate in platform-based commerce. However, most MSEs operate without adequate understanding of legal obligations under Indonesia's Personal Data Protection Law (Law No. 27 of 2022) and e-commerce regulations, particularly regarding privacy policies and terms & conditions. This qualitative research examined the effectiveness of legal mentoring programs in enhancing digital legal literacy among 45 MSE operators in Jakarta and Yogyakarta. Through thematic analysis of semi-structured interviews, focus group discussions, and document review, the study identified critical knowledge gaps in data protection compliance, contractual obligations, and platform-specific legal requirements. The findings reveal that structured mentoring interventions focusing on policy documentation significantly improved participants' capacity to formulate legally compliant privacy policies and terms & conditions tailored to platform operations. The research proposes a community-based digital legal literacy framework that integrates state-led policy guidance, peer mentoring networks, and accessible legal resources. These mechanisms are essential for MSEs to navigate the complexities of the platform economy while protecting both consumer rights and business sustainability in Indonesia's evolving digital landscape